Pemuridan Kontekstual sebagai Strategi Pendidikan Kristen di Masyarakat Multikultural - Immanuela Deru; Indriati Tjipto Purnomo; Joshua Christian Wenas; Simon Simare-mare (Sekolah Tinggi Teologia Kerusso Indonesia, 2025)
This study aims to analyze contextual discipleship as a strategy for Christian education in a multicultural society. The study uses a mixed-methods approach with a convergent design to obtain a comprehensive understanding of the effectiveness of discipleship in shaping the character and spirituality of students. Quantitative data were collected through surveys, while qualitative data were gathered through in-depth interviews and focus group discussions. The results show that contextual discipleship plays a significant role in strengthening faith understanding, fostering tolerance, encouraging social involvement, and shaping students to be more responsive to the challenges of technological development and digital culture. Contextual discipleship proves to be effective when implemented consistently, based on mentoring relationships, and capable of translating Gospel values into the students' social context. This study concludes that contextual discipleship is a strategic approach that can present holistic, transformative, and relevant Christian education amidst diversity. Contextual discipleship allows Christian education to have a greater impact in shaping character that aligns with the demands of the times and contextualizing faith values in everyday life.